Zinc oxide nanoparticles-based reduced graphene oxide composites for photocatalytic and photovoltaic applications / Majid Azarang - Majid, Azarang (2017)
Zinc oxide nanoparticles and reduced graphen oxide (rGO) composites were synthesized using the sol-gel method in a starch environment. Different concentrations effects of graphene oxide (GO) on the structure and optical properties of ZnO nanoparticles (NPs) were investigated. X-ray diffraction patterns (XRD) and Fourier transform infrared spectroscopy (FTIR) indicated that the GO sheets were reduced and changed to reduced graphene oxide (rGO) during the calcination of the composites at 350 °C. In addition, the XRD patterns of the NPs indicated a hexagonal (wurtzite) structure for all the products. Field emission scanning electron and transmission electron microscope (FESEM and TEM) images showed that the NPs were decorated and dispersed on the rGO sheets very well. In addition, high resolution TEM, HRTEM images revealed that the rGO concentration had an effect on the crystal growth process for the ZnO NPs. Furthermore, these studies showed that the NPs could be grown with a single crystal quality in an optimum rGO concentration. According to the XRD results that were obtained from pure ZnO NPs, the calcinations temperature was decreased by the rGO. Optical studies showed that the optical properties of the ZnO+rGO composite were affected by the rGO concentration. Finally, the obtained ZnONPs+rGO composite was used as photocatalyst to remove methylene blue (MB). Observations showed that the efficiency of the photocatalyst activity of the ZnONPs was significantly increased by GO. In addition, the ZnO+rGO composite was used to generate a photocurrent device. Observations showed that the photocurrent intensity of the composite was dramatically increased by increasing the rGO concentration, with an optimum rGO concentration.